3D‐Printed Wood‐Fiber Reinforced Architected Cellular Composites. Issue 11 (24th November 2020) - Estakhrianhaghighi, Ehsan; Mirabolghasemi, Armin; Zhang, Yingnan; Lessard, Larry; Akbarzadeh, Abdolhamid
Abstract : Wood‐fiber reinforced PLA architected composites offer a strategy for 3D printing of sustainable advanced materials with enhanced thermomechanical properties out of low‐cost waste materials through an optimized material composition and the rational design of underlying microarchitectures. Further details can found in the article, number 2000565, Abdolhamid Akbarzadeh, and co‐workers.